Middelalderlig godsadministration i Danmark - Hybel, Nils (Historisk Tidsskrift, 2013)
Manorial Administration in Denmark in the Middle AgesThe formation of landed estates in Denmark was closely linked with ecclesiastical and monastic expansion. The earliest evidence of large landed properties is from the end of the eleventh century. Its accumulation was one of the characteristic traits of the Middle Ages, and by the end of the period Danish landed estates were concentrated in the hands of a very small number of proprietors. Various administrative methods were used in an attempt to optimise the utilization of these estates, which were the basic resource for the aristocracy’s livelihood and activities. The aristocracy began consolidating their properties in the twelfth century, where we see the first signs of large-scale production in the 1130s. This development continued up through the High Middle Ages within the framework of a farming system, supplemented perhaps by direct management of a few estates. In the fourteenth century Danish manorial estates were comparable in size to those in the rest of Europe. In Denmark there are no traces of labour services during the High Middle Ages, but it was not insignificant in the fourteenth century. Labour service was as a rule linked to directly managed estates. The first Danish surveys mention unspecified labour services, week work, and boon services, but wage labour was an essential element in large-scale production in the High Middle Ages. With respect to labour services and wage labour, Danish manors in the fourteenth century were in principle operated no differently than English manors in the thirteenth century. The farming system was prevalent in the fourteenth century, but the large manors of the Bishop of Roskilde around that city and in eastern and northern Zealand were managed directly by the bishop’s bailiffs. This was also true of Brink, the bishop of Ribe’s manor near the coastal mudflats. The number of Danish manors declined in the Late Middle Ages, especially the smaller ones, and with it the frequency of farming. There thus emerges a clearer picture of a form of direct management comparable to what has been called the »classic« form of Western European large-scale manorial production based on labour services in the High Middle Ages. It should be stressed, however, that peasant farming was the predominant economic element in Denmark throughout the entire Middle Age period, also in the fourteenth century, when large-scale production was at its peak. In the Middle Ages the manorial landowner was more of a rentier than an administrator of his own lands.Translated by Michael Wolfe